2011
DOI: 10.4049/jimmunol.1102533
|View full text |Cite
|
Sign up to set email alerts
|

Alloantibodies against MHC Class I: A Novel Mechanism of Neonatal Pancytopenia Linked to Vaccination

Abstract: Fetal/neonatal alloimmune thrombocytopenia is a frequent disease in humans where alloantibodies against platelet Ags lead to platelet destruction and hemorrhage. Although a role in the disease for Abs against MHC has been suspected, this has not been formally demonstrated. Since 2007, a hemorrhagic syndrome due to thrombocytopenia and designated as bovine neonatal pancytopenia (BNP) has been recognized in calves in several European countries. An inactivated antiviral vaccine is strongly suspected to be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 44 publications
4
41
1
Order By: Relevance
“…To manufacture this vaccine, BVD virus is cultured in Madin-Darby bovine kidney (MDBK) cells [30] and, following purification, combined with a novel proprietary adjuvant (Procison-A TM ; a micro-fluidized oil-in-water adjuvant composed of Quil-A, Cholesterol, mineral oil [31]). High levels of residual bovine proteins have been detected in Pregsure© [8,9,32] and alloantibodies from BNP cows have been shown to recognize MDBK cells [8,9,12,19]. Furthermore, experimental immunization of calves with Pregsure© confirmed that vaccination induces alloantibodies that bind MDBK cells and leukocytes [10,19].…”
Section: Vaccination Induces Bnp-associated Alloantibodiesmentioning
confidence: 77%
See 4 more Smart Citations
“…To manufacture this vaccine, BVD virus is cultured in Madin-Darby bovine kidney (MDBK) cells [30] and, following purification, combined with a novel proprietary adjuvant (Procison-A TM ; a micro-fluidized oil-in-water adjuvant composed of Quil-A, Cholesterol, mineral oil [31]). High levels of residual bovine proteins have been detected in Pregsure© [8,9,32] and alloantibodies from BNP cows have been shown to recognize MDBK cells [8,9,12,19]. Furthermore, experimental immunization of calves with Pregsure© confirmed that vaccination induces alloantibodies that bind MDBK cells and leukocytes [10,19].…”
Section: Vaccination Induces Bnp-associated Alloantibodiesmentioning
confidence: 77%
“…Furthermore, serum and colostrum from BNP cows were shown to contain alloantibodies that bind to peripheral blood leukocytes, platelets and bone marrow cells [9,11,12,[18][19][20][21], and intravenous infusion of these antibodies was sufficient to induce the disease [9]. The bovine epitheliochorial placenta presents a complete barrier to the transfer of immunoglobulins from the cow to the fetus, and thus the calf is completely dependent on ingestion of colostrum for maternal immunoglobulin transfer [22], explaining why BNP only occurs postpartum.…”
Section: Bnp Is An Alloimmune Disease Induced By Antibodies Absorbed mentioning
confidence: 99%
See 3 more Smart Citations